Climate Smart Agriculture Sustainability: A Multidimensional Assessment - Aryyana Hasyim; Harsuko Riniwati; Dini Atikawati (Pusbindiklatren Bappenas, 2025)
Indonesia has a serious problem of climate change that impacts the production of rice in the country, particularly in the climate-sensitive areas of Lombok Tengah. To alleviate the risks of these, the government promotes Climate Smart Agriculture (CSA), which is not commonly practiced. The paper uses the Multidimensional Scaling (MDS) technique of measuring the sustainability of CSA implementation by applying the Rap-CSA method. This method measures five dimensions of sustainability: ecological, economic, social, technological, and institutional. A structured questionnaire was administered in the local language to 75 farmers who participated in field trials at the CSA demonstration sites. These findings demonstrate that three dimensions, including social (79.90%), ecological (75.02%), and institutional (79.73%), are very sustainable. Conversely, the technological (55.75%) and economic (39.33%) performance is moderate and less sustainable, respectively. The sustainability index of CSA has a total mark of 66.14, which is average. The findings imply that economic and technological factors need to be altered to facilitate the implementation of CSA with a more balanced, robust orientation.